Reigniting tobacco control: returning Australia to the front of the pack - Becky Freeman (Sax Institute, 2023)
Australia has long been heralded as a leader in tobacco control, but more than 10 years have passed since the country implemented the world's first tobacco plain packaging reforms. In late 2022, the Australian Federal Government announced it would be "reigniting the fight against tobacco addiction". The forthcoming reforms package will help modernise and re-energise Australian tobacco control. The Government has signalled that preliminary reforms will include updating graphic health warnings, standardising tobacco pack sizes and filters, and banning menthol and flavours. The recently endorsed National Tobacco Strategy 2023-2030 also opens the door to further supply-side reforms. Ten years ago, when Australia fought multiple legal challenges from the tobacco industry and established plain packaging as a best practice standard, e-cigarette or vaping products were a fringe issue with little presence in Australia. Today, vaping product use by young Australians has dramatically and rapidly increased. Easy access and marketing of cheap, flavoured, disposable, nicotine-containing vaping products are driving use. Recognising that the current approach to e-cigarette regulation is not achieving its aim of preventing children and adolescents from accessing vaping products, the Australian Therapeutic Goods Administration (TGA) launched a consultation on possible reforms in late 2022. Currently, vaping importers and retailers are exploiting an exemption for non-nicotine products in regulations, and nicotine-containing products are masquerading as non-nicotine products. The ideal public health solution would see the elimination of all vaping product sales, nicotine and non-nicotine alike, that fall outside of the TGA prescription-only access pathway. After 10 years of minimal action, it is invigorating to have three key initiatives in play to fully "reignite" tobacco control - the tobacco legislation renewal and update, the imminent national strategy release, and the TGA consultation on vaping products. Re-establishing Australia as a tobacco control leader is welcome news for public health.